1994
DOI: 10.2307/2389824
|View full text |Cite
|
Sign up to set email alerts
|

On the Temperature Dependence of Soil Respiration

Abstract: 1. From previously published measurements of soil respiration rate (R) and temperature (T) the goodness of fit of various R vs T relationships was evaluated. 2. Exponential (Q10) and conventional Arrhenius relationships between T and R cannot provide an unbiased estimate of respiration rate. Nor is a simple linear relationship appropriate. 3. The relationship between R and T can, however, be accurately represented by an Arrhenius type equation where the effective activation energy for respiration varies invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

110
2,650
18
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,539 publications
(2,867 citation statements)
references
References 39 publications
110
2,650
18
20
Order By: Relevance
“…Soil respiration is generally strongly influenced by soil temperature (Singh and Gupta, 1977;Lloyd and Taylor, 1994); in our study, despite a very small temperature range (<4 C), soil temperature at 0e10 cm depth explained 24e42% of the variation in soil respiration when roots were present, while in the trenched subplots, soil respiration was only related to soil temperature in the litter removal treatments. Increased sensitivity of soil respiration in the presence of roots has previously been shown for temperate forests (Boone et al, 1998) and it appears that a similar relationship may exist in tropical forests even though they have a much smaller range in soil temperatures.…”
Section: Treatment Effects On the Relationships Between Soil Respiratcontrasting
confidence: 47%
“…Soil respiration is generally strongly influenced by soil temperature (Singh and Gupta, 1977;Lloyd and Taylor, 1994); in our study, despite a very small temperature range (<4 C), soil temperature at 0e10 cm depth explained 24e42% of the variation in soil respiration when roots were present, while in the trenched subplots, soil respiration was only related to soil temperature in the litter removal treatments. Increased sensitivity of soil respiration in the presence of roots has previously been shown for temperate forests (Boone et al, 1998) and it appears that a similar relationship may exist in tropical forests even though they have a much smaller range in soil temperatures.…”
Section: Treatment Effects On the Relationships Between Soil Respiratcontrasting
confidence: 47%
“…The effect of temperature on Rs has been illustrated in a wide range of studies (Eliasson et al, 2005;Fierer et al, 2005;Lloyd and Taylor, 1994;Tucker et al, 2013). Biasi et al (2005) reported that temperature could influence the utilization of carbon source by microbes or microbial metabolism leading to Rs rate changes.…”
Section: Effects Of Temperature and Oxygenmentioning
confidence: 99%
“…A commonly used method is that proposed by Lloyd and Taylor (1994) who link net ecosystem respiration to soil temperature. This present study used the approach of Lloyd (2006) and Rowson (2007) that both identified depth to the water table as a significant factor in controlling net ecosystem respiration.…”
Section: Surface Exchange Of Comentioning
confidence: 99%
“…The first row of figures in the brackets represents the probability that the coefficient is equal to zero, and the second row of figures in brackets represents the standard error in the coefficient. This has several advantages over the approach of Lloyd and Taylor (1994). Firstly, it is stated in terms of the air temperature rather than the soil temperature the former being more likely to be measured over longer periods within a catchment and thus enabling better extrapolation of the results.…”
Section: Surface Exchange Of Comentioning
confidence: 99%